A fully linear 5.2 GHz - 5.8 GHz digitally controlled oscillator in 65-nm CMOS technology. (August 2019) - Heydarzadeh, Siavash; Torkzadeh, Pooya; Sadughi, Sirus
Abstract: A low-power fully linear integrated CMOS LC-based Digitally Controlled Oscillator is presented. The DCO operates in 5.2 GHz to 5.8 GHz range for using in IEEE 802.11a wireless applications. The system has been designed using 65 nm CMOS technology and 1.2 V supply voltage. By applying a proposed filter in DCO architecture −133.41 dBc/Hz phase noise at 1 MHz offset frequency from the fundamental carrier is achieved. The code generator and digital to analog converter designed to provide the high precision voltage required for fine-tuning. The output frequency swept through 10 control bits with 100 KHz resolution. The measured RMS jitter (∑ [1 KHz – 2 GHz]) from 5.8 GHz carrier is 1.65 fs. The core chip occupied 400 μm × 702 μm area and consumed 2.1 mA current.